Introducing Our New Chief Editor - Mark Yorek (Journal of Diabetes Research)
Journal of Diabetes Research is delighted to announce the installation of Dr. Mark Yorek as the new Chief Editor for the journal. In this Editorial, Dr. Yorek discusses his research background, his ideas for the journal’s development, and his views on the direction of the field of diabetes.